Quantum Confinement Effect in Strained-Si¬1-xGex Double-Gate Tunnel Field-Effect Transistors - Nguyễn, Đăng Chiến (IEEE Publishing, 2024)
The energy bandgap is a key factor to determine the tunneling current in tunnel field-effect transistors (TFETs). This paper numerically investigates the effect of quantum confinement in the double-gate TFETs by evaluating the effective energy-band bandgap of the ultra-thin strained-Si1-xGex body. The band-offset caused by the quantum confinement effect is rapidly increased with increasing the Ge mole fraction because the body thickness must be decreased to retain the same compressive strain of Si1-xGex. A medium Ge more fraction of strained-Si1-xGex is favorable to optimize the device performance in the strained-Si1-xGex double-gate TFETs.